Aplikasi Pestisida Nabati Daun Pepaya Pada Tanaman Cabai Di Lahan Kelompok Tani Diporejo Desa Kedayunan Kabupaten Banyuwangi - Akyun, Surotun; Indraloka, Aldy Bahaduri; Alfiyah, Nurul; Yuniwati, Ika (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
The Diporejo Farmers Community, Kedayunan Village in Banyuwangi Regency, has quite high potential for agricultural waste product from cultivating papaya (Carica papaya). If agricultural waste was not utilized properly, it caused problems in the form of pollution of surrounding environment, disturbing the surroundings and becoming a source of disease. The aim of this Community Service activity is to assist farmer community in developing papaya waste product into natural pesticides. Several series of community service activities have been carried out, such as: 1) conducting socialization on natural pesticides and 2) carrying out the practice of making natural pesticides. Further service activities carried out are 3) production of pesticides independently and periodically by groups of farmers, and 4) application of pesticides on chili cultivation. The results of monitoring carried out for approximately 3 months showed that plant-based pesticides made from papaya leaves were applied as a form of prevention against OPT (Plant Pest Organisms), farmer groups were able to produce plant-based pesticides independently and continuously, the intensity of pests caught in yellow traps installed on chili plants experienced a significant decline.